“The Good, the Bad, and the Ugly” – About Diverse Phenotypes of Hepatic Stellate Cells in the LiverSummary - Alexandra Bogomolova; Asha Balakrishnan; Michael Ott; Amar Deep Sharma (Cellular and Molecular Gastroenterology and Hepatology, 2024)
Hepatic stellate cells (HSCs) and their activated derivatives, often referred to as myofibroblasts (MFs), play a key role in progression of chronic liver injuries leading to fibrosis, cirrhosis, and hepatocellular carcinoma. Until recently, MFs were considered a homogenous cell type majorly due to lack of techniques that allow complex molecular studies at a single-cell resolution. Recent technical advancements in genetic lineage-tracing models as well as the exponential growth of studies with single-cell transcriptome and proteome analyses have uncovered hidden heterogeneities among the HSC and MF populations in healthy states as well as chronic liver injuries at the various stages of tissue deformation. The identification of different phenotypes along the HSC/MF axis, which either maintain essential liver functions (“good” HSCs), emerge during fibrosis (“bad” HSCs), or even promote hepatocellular carcinoma (“ugly” HSCs), may lay the foundation for targeting a particular MF phenotype as potential treatment for chronic liver injuries.